Building community trust and financial inclusion through online religious leaders and digital communication: Evidence from Islamic banking in Indonesia - Mulyanti , Kurniawati; Nugroho, Aris Setyanto; Darmansyah , Darmansyah (Central Community Development Journal, 2025)
Online Religious Leader, online advertising and management performance are factors that will influence the existence of Islamic banks. These factors are important for Bank Syariah Indonesia because they impact consumer trust and decisions regarding the use of Islamic bank products in Indonesia. Therefore, banks must understand and adapt to the challenges of future competition. This study aims to evaluate and develop the influence of the variables of online Religious Figures, Online Advertising and Management Performance on trust and its implications for the decision to become a customer of Bank Syariah Indonesia. This study used a quantitative descriptive survey with a population of all Bank Syariah Indonesia customers in Jakarta, Bogor, Depok, Tangerang, and Bekasi. A total of 320 samples were collected. This study uses cross-sectional data from various respondents at a certain point in time. Thus, the influence of one factor on another is assumed to occur instantly at the same time. The analysis technique of data processing results in this study is PLSs and Structural Equation Modeling, which are used to determine the influence of variables in this study. Research shows that online religious leaders have a direct, indirect, and significant influence on the decision to become a customer of Bank Syariah Indonesia. Likewise, online advertising significantly influences the decision to become a Bank Syariah Indonesia customer. The performance of Bank Syariah Indonesia Management significantly influences the decision to become a customer of Bank Syariah Indonesia. The findings of this study are novel in banking marketing and consumer behavior, especially those related to understanding the integrative model of the Theory of Reason Action and Stimulus Organism Response to increase the Decision to Become a Customer of Bank Syariah Indonesia.